Roles of clinical practice guidelines outside the clinical encounter - Florez, Ivan Dario (My University, 2020)
Clinical practice guidelines (CPGs) are statements that include recommendations intended to optimize patient care that are informed by a systematic review of evidence and an assessment of the benefits and harms of alternative care options. CPGs’ recommendations have traditionally focused on informing clinicians and patients on the best options, i.e., supporting decisions that occur at the clinical encounter level. Considering all their advantages (a systematic and comprehensive review of the evidence, a multidisciplinary team assessing the evidence and balancing benefits and harms, and the additional considerations such as patients’ preferences, implementability and feasibility of interventions and their costs) CPGs have also become powerful tools to inform decisions and activities outside the clinical encounter. This, because the clinical encounter cannot be completely separated from other decisions that indirectly affect that level, such as those related to quality improvement activities and economic decisions in healthcare. Moreover, activities that are not directly related to the clinical encounter can benefit from CPGs, like education and licensing activities and research prioritization processes, or judicial decisions. The role of CPGs in all these activities has been neglected in the literature. In this study, I performed a critical interpretive synthesis of the literature to summarize the different roles CPGs play outside the clinical encounter and to understand how, and under what conditions CPGs are used in these roles. I also conducted an international survey to describe how frequent these roles exist, from the CPGs developers' perspectives. Lastly, I conducted a multiple case study to understand how and under what conditions CPGs play one of the main roles outside the clinical encounter (drug funding decisions), in two different settings (Colombia and Canada/Ontario). Based on the results, I developed a framework to describe and categorize the roles of CPGs outside the clinical encounter and to determine how and under what conditions CPGs are used in these roles. I highlighted the key areas that require additional methodological research and categorize the roles in main, secondary and unanticipated roles. I also described how international developers reported that CPGs play these roles and how these roles are part of their CPGs final aims in the second study. Lastly, in the case study, I revealed that CPGs were instrumentally used to inform one of the main roles, drug funding decisions, in the Colombian case, and they had a minor conceptual use in the case of Canada/Ontario.
Keywords: guidelines; quality improvement; coverage decisions; drug reimbursement; evidence-based medicine; medical education; research prioritization; research gaps; medical litigation; judicial decisions; maintenance of certification; accreditation